Reading comprehension in face-to-face and web-based modalities: graduate students’ use of reading and language learning strategies in EFL1 - Arismendi Gómez, Fabio Alberto; Colorado López, Doris; Grajales Marin, Luisa Fernanda (Colombian Applied Linguistics Journal, 2011)
Few studies in Colombia have explored and compared students’ reading comprehension processes in EFL, in different modalities of instruction. This article reports on some findings of a larger study in which two groups of graduate Law students took a reading comprehension course in English, delivered in two different modalities of instruction: face-to-face and web-based. Both courses were served by an English teacher from the School of Languages at Universidad de Antioquia. The data gathered from class observations, in-depth interviews, questionnaires, tests, the teacher’s journal and data records in the platform provided insights about the students’ use of reading and language learning strategies in both modalities. Findings suggest that students applied the reading strategies explicitly taught during the courses and some language learning strategies for which they did not receive any instruction.